112k views
15 votes
PICTURE DOWN BELOW!!! if anyone can help answer these please do!

PICTURE DOWN BELOW!!! if anyone can help answer these please do!-example-1
User Jeris
by
4.7k points

1 Answer

5 votes

Answer:

Step-by-step explanation: Subtract b from both sides to isolate mx :

y - b = mx + b - b

y - b = mx

STEP 2 :

Divide both sides by x in other to isolate x

(y - b) / m = mx / m

(y - b) /m = x

Therefore, making x the subject gives the final equation as : x = (y - b) /m

User Pavel Paulau
by
5.0k points